Decrease in Blood Neutrophil-to-Lymphocyte Ratio Indicates Better Survival After Neoadjuvant Chemotherapy in Patients With Advanced Gastric Cancer - Liu, Ziyi; Liang, Yahang; Tang, Xiaolong; Qu, Hui (Frontiers in Surgery, 2021)
Introduction: Gastric cancer is the fifth most commonly diagnosed tumor and is the fourth leading cause of cancer-related mortality, worldwide. Due to the low rate of early diagnosis, approximately two-thirds of patients are first diagnosed at an advanced stage. Neoadjuvant chemotherapy (NAC) is recommended for advanced gastric cancer (AGC) patients. The neutrophil-to-lymphocyte ratio (NLR), a combined inflammatory and immunogenic factor has been universally used for predicting outcomes in AGC patients. Given that NLR is a dynamic process, in this study, we investigated the value of NLR change for the prediction of chemotherapeutic responses and prognosis in AGC patients. Methods: We retrospectively enrolled 111 AGC patients who underwent NAC following curative surgery. Patients were divided into two groups according to the NLR change after chemotherapy into the increased and decreased groups. Outcome measures were overall survival (OS) and disease-free survival (DFS). Univariate was calculated by Kaplan-Meier method. Multivariate analysis was performed using the Cox proportional hazards regression model. Results: Post-chemotherapy NLR increased in 36 patients and decreased in 75 patients. After a median follow-up time of 19 months, six patients developed local recurrence, 23 developed distant recurrence, and 34 died. Patients with reduced post-chemotherapy NLR showed significantly longer OS (P<0.001) and DFS (P<0.001). A decrease in the NLR after NAC was an independent indicator associated with better OS (P<0.001) and DFS (P<0.001). Conclusions: In AGC patients, a decrease in NLR after NAC indicated better survival. NLR change could serve as a robust indicator for the efficiency of NAC and prognostic prediction in AGC patients.